Global burden of COPD. Issue 1 (23rd October 2015) - López‐Campos, José Luis; Tan, Wan; Soriano, Joan B.
Abstract: It is estimated that the world population will reach a record 7.3 billion in 2015, and the high burden of chronic conditions associated with ageing and smoking will increase further. Respiratory diseases in general receive little attention and funding in comparison with other major causes of global morbidity and mortality. In particular, chronic obstructive pulmonary disease (COPD) has been a major public health problem and will remain a challenge for clinicians within the 21st century. Worldwide, COPD is in the spotlight, since its high prevalence, morbidity and mortality create formidable challenges for health‐care systems. This review emphasizes the magnitude of the COPD problem from a clinician's standpoint by drawing extensively from the new findings of the Global Burden of Disease study. Updated, distilled information on the population distribution of COPD is useful for the clinician to help provide an appreciation of the relative impact of COPD in daily practice compared with other chronic conditions, and to allocate minimum resources in anticipation of future needs in care. Despite recent trends in reduction of COPD standardized mortality rates and some recent successes in anti‐smoking efforts in a number of Western countries, the overarching demographic impact of ageing in an ever‐expanding world population, joined with other factors such as high rates of smoking and air pollution in Asia, will ensure that COPD will continue to pose an ever‐increasing problem well into the 21st century.